2021
DOI: 10.33590/emjmicrobiolinfectdis/20-00215
|View full text |Cite
|
Sign up to set email alerts
|

The PPE Pandemic: Sex-Related Discrepancies of N95 Mask Fit

Abstract: During the COVID-19 pandemic, caused by the severe acute respiratory syndrome coronavirus 2, healthcare professionals across the world have been at high risk of transmission because of their direct contact with infected patients. In October 2020, the International Council of Nurses (ICN) confirmed that 1,500 nurses had died from COVID-19 in 44 countries and estimated that healthcare worker COVID-19 fatalities worldwide could be more than 20,000. To ensure protection of healthcare personnel, properly fitting pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Eight studies looked at the effect of gender on fitting ability [ 32 , 37 , 66 , 78 , 89 , 107 , 111 , 114 , 117 ], with four of these highlighting that males had a higher pass rate than females [ 66 , 89 , 111 , 117 ]. Christopher et al highlighted the reasons for failing the fit test for females, including facial asymmetry (8%), small bones (77%), and none reported (15%), and the reasons for males, including facial hair (91%), large bones (3%), and small bones (6%) [ 89 ]. In the study by Williams et al, although males had a higher passing rate than females; however, females were fitted with the 3M 9320A more often than males (7.3% vs. 1.5%, p< 0.001) [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight studies looked at the effect of gender on fitting ability [ 32 , 37 , 66 , 78 , 89 , 107 , 111 , 114 , 117 ], with four of these highlighting that males had a higher pass rate than females [ 66 , 89 , 111 , 117 ]. Christopher et al highlighted the reasons for failing the fit test for females, including facial asymmetry (8%), small bones (77%), and none reported (15%), and the reasons for males, including facial hair (91%), large bones (3%), and small bones (6%) [ 89 ]. In the study by Williams et al, although males had a higher passing rate than females; however, females were fitted with the 3M 9320A more often than males (7.3% vs. 1.5%, p< 0.001) [ 111 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies concluded the negative effects of facial hair on fitting capability [ 38 , 89 , 115 , 139 ]. Another point is that the influence of facial hair on the fitting capability of surgical masks was less than that of the FFP3 respirators.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations